Differences in the symptom profile of methamphetamine-related psychosis and primary psychotic disorders. (May 2017) - McKetin, Rebecca; Baker, Amanda L.; Dawe, Sharon; Voce, Alexandra; Lubman, Dan I.
Abstract: We examined the lifetime experience of hallucinations and delusions associated with transient methamphetamine-related psychosis (MAP), persistent MAP and primary psychosis among a cohort of dependent methamphetamine users. Participants were classified as having (a) no current psychotic symptoms, (n=110); (b) psychotic symptoms only when using methamphetamine (transient MAP, n=85); (c) psychotic symptoms both when using methamphetamine and when abstaining from methamphetamine (persistent MAP, n=37), or (d) meeting DSM-IV criteria for lifetime schizophrenia or mania (primary psychosis, n=52). Current psychotic symptoms were classified as a score of 4 or more on any of the Brief Psychiatric Rating Scale items of suspiciousness, hallucinations or unusual thought content in the past month. Lifetime psychotic diagnoses and symptoms were assessed using the Composite International Diagnostic Interview. Transient MAP was associated with persecutory delusions and tactile hallucinations (compared to the no symptom group). Persistent MAP was additionally associated with delusions of reference, thought interference and complex auditory, visual, olfactory and tactile hallucinations, while primary psychosis was also associated with delusions of thought projection, erotomania and passivity. The presence of non-persecutory delusions and hallucinations across various modalities is a marker for persistent MAP or primary psychosis in people who use methamphetamine. Highlights: Transient MAP was associated with persecutory delusions and tactile hallucinations. Persistent MAP was additionally associated with various other hallucinations and delusions. There was no significant difference in the symptom profile of persistent MAP and primary psychosis.